2(3) central composite rotatable design for the production of neem oil nanoemulsion for antifungal and antiparasitic applications - Rabelo, Alessandra S.; Sutili, Felipe K. [UNESP]; Meneses, Juliana O.; Severino, Patricia; Souto, Eliana B.; Fujimoto, Rodrigo Y.; Cardoso, Juliana C. (Wiley-Blackwell, 2020)
BACKGROUND The present study describes the design and production of an oil-in-water nanoemulsion composed of neem oil as the inner phase for use as an antifungal and antiparasitic control in aquaculture. A 2(3) central composite rotatable design adopting surface response was used as the experimental design, setting the neem oil concentration (4-15%), surfactant concentration (0.5-10%) and sonication power (20-90%) as the independent variables, while the droplet size, polydispersity index (PDI) and zeta potential were set as the response (dependent) variables. RESULTS Droplet size and PDI showed the best results using the sonication method with 5 min of process. The coefficients of determination were greater than 0.900 for all response. The best formulation was obtained with 9% of neem oil and 5.25% of polysorbate 20. CONCLUSION Antifungal activity of the optimized nanoemulsion against Saprolegnia parasitica was demonstrated, also attributed to the presence of the surfactant. Concentrations of 200 mg L-1 of nanoemulsion resulted in 100% parasitic mortality. (c) 2020 Society of Chemical Industry
Keywords: emulsions; neem oil; ultrasonic; antifungal; antiprotozoal; experimental design